Active Faulting Geometry and Stress Pattern Near Complex Strike‐Slip Systems Along the Maghreb Region: Constraints on Active Convergence in the Western Mediterranean. Issue 9 (22nd September 2018) - Soumaya, Abdelkader; Ben Ayed, Noureddine; Rajabi, Mojtaba; Meghraoui, Mustapha; Delvaux, Damien; Kadri, Ali; Ziegler, Moritz; Maouche, Said; Braham, Ahmed
Abstract: The Maghreb region (from Tunisia to Gibraltar) is a key area in the western Mediterranean to study the active tectonics and stress pattern across the Africa‐Eurasia convergent plate boundary. In the present study, we compile comprehensive data set of well‐constrained crustal stress indicators (from single focal mechanism solutions, formal inversion of focal mechanism solutions, and young geologic fault slip data) based on our and published data analyses. Stress inversion of focal mechanisms reveals a first‐order transpression‐compatible stress field and a second‐order spatial variation of tectonic regime across the Maghreb region, with a relatively stable SHmax orientation from east to west. Therefore, the present‐day active contraction of the western Africa‐Eurasia plate boundary is accommodated by (1) E‐W strike‐slip faulting with reverse component along the Eastern Tell and Saharan‐Tunisian Atlas, (2) a predominantly NE trending thrust faulting with strike‐slip component in the Western Tell part, and (3) a conjugate strike‐slip faulting regime with normal component in the Alboran/Rif domain. This spatial variation of the present‐day stress field and faulting regime is relatively in agreement with the inferred stress information from neotectonic features. According to existing and newly proposed structural models, we highlight the role of main geometrically complex shear zones in the present‐day stress pattern of the Maghreb region. Then, different geometries of these major inherited strike‐slip faults and its related fractures (V‐shaped conjugate fractures, horsetail splays faults, and Riedel fractures) impose their component on the second‐ and third‐order stress regimes. Neotectonic and smoothed present‐day stress map (mean SHmax orientation) reveal that plate boundary forces acting on the Africa‐Eurasia collisional plates control the long wavelength of the stress field pattern in the Maghreb. The current tectonic deformations and the upper crustal stress field in the study area are governed by the interplay of the oblique plate convergence (i.e., Africa‐Eurasia), lithosphere‐mantle interaction, and preexisting tectonic weakness zones. Key Points: Maghreb region is characterized by different geometries of active strike‐slip faults Present‐day active contraction on western Africa‐Eurasia boundary is accommodated by a combination of strike‐slip and thrust faulting Second‐order tectonic regime across Maghreb varies with clockwise rotation of SHmax from east to west